Produção e caracterização de painel de anticorpos monoclonais e identificação de antígenos de Babesia bovis - Joely Ferreira Figueiredo (1997)
With the aim of identifying antigens of Babesia bovis, with potencialuse in immunodiagnostic tests, a panel of monoclonal antibodies wasproduced and characterized by the indirect fluorescent antibody test,ELISA and Westem blotting. The resultant hybrids, after fusion wereselected by the indirect fluorescent antibody test, cloned, maintained in vitro culture and cryopresewed in liquid nitrogen. Twelve clonesproducing monoclonal antibodies reacted against merozoites, while fivereacted on the surface of merozoites and one clone reacted against the ,polar region of merozoites. All monoclonal antibodies reacted inELISA. with optical density varying Som 0.365 to 0.502 (cut-off =0.022). The bands recognized by the monoclonal antibodies in Westemblotting had molecular weights ranging from 162 to 19 kDa. Fourclones recognized only one band of 73 l<.Da and the other did not reactin Westem blotting. These antigens will be usetiil for the developmentof more sensitive and especific immunodiagnostic tests for use inepidemiological studies on bovine babesiosis in Brazil.